AN EXPLORATORY STUDY ON THE WORK-LIFE BALANCE OF WOMEN ENTREPRENEURS IN SOUTH INDIA - Rincy V. Mathew; N. Panchanatham (Asian Academy of Management Journal, 2011)
In India, entrepreneurship has traditionally been considered a male prerogative. However, in tandem with a changing socio-cultural environment and an increase in educational opportunities, women have started recognising their inherent talents and business skills. With the help of various governmental and non-governmental agencies, growing numbers of women are joining the ranks of entrepreneurs. However, in the existing familial and societal setup, entrepreneurial women are overburdened and find it increasingly difficult to balance their work and life roles. Therefore, the major objective of the present study was to develop and validate an appropriate tool to illustrate the work-life balance (WLB) issues faced by women entrepreneurs of South India. We also sought to understand the important factors influencing the WLB of these women entrepreneurs. To achieve this end, data were collected by area sampling (cluster-random) paired with semi-structured interviews and a questionnaire. The generated data were subjected to standard statistical procedures, such as factor analysis, regression analysis, analysis of variance (ANOVA) and student’s t-test. The five-point psychometric tool developed consisted of 39 statements related to five factors. Each of the statements possessed adequate reliability and validity. This study revealed that role overload, dependent care issues, quality of health, problems in time management and lack of proper social support are the major factors influencing the WLB of women entrepreneurs in India. Furthermore, even though the vast majority of the entrepreneurs examined in this study suffers from WLB issues, there are significant differences in the level of WLB issues faced by the various categories of women entrepreneurs. The present study provides recommendations for human resource professionals, management consultants, academicians and women entrepreneurs themselves to deal with the major WLB issues faced by Indian women entrepreneurs.